2010
DOI: 10.1044/1092-4388(2010/09-0005)
|View full text |Cite
|
Sign up to set email alerts
|

Lip Movement Exaggerations During Infant-Directed Speech

Abstract: Purpose Although a growing body of literature has indentified the positive effects of visual speech on speech and language learning, oral movements of infant-directed speech (IDS) have rarely been studied. This investigation used 3-dimensional motion capture technology to describe how mothers modify their lip movements when talking to their infants. Method Lip movements were recorded from 25 mothers as they spoke to their infants and other adults. Lip shapes were analyzed for differences across speaking cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 74 publications
1
58
0
Order By: Relevance
“…It has been suggested that newborn infants have a preference for attending to faces (Goren, Sarty, & Wu, 1975; Morton & Johnson, 1991; Simion, Valenza, Macchi-Cassia, Turati, & Umilta, 2002). Furthermore, adults pattern their input to infants to enhance facial cues, exaggerating visual prosodic cues during infant-directed speech (Green, Nip, Wilson, Mefferd, & Yunusova, 2010). Facial cues therefore likely provide an early, salient cue to linguistic structure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that newborn infants have a preference for attending to faces (Goren, Sarty, & Wu, 1975; Morton & Johnson, 1991; Simion, Valenza, Macchi-Cassia, Turati, & Umilta, 2002). Furthermore, adults pattern their input to infants to enhance facial cues, exaggerating visual prosodic cues during infant-directed speech (Green, Nip, Wilson, Mefferd, & Yunusova, 2010). Facial cues therefore likely provide an early, salient cue to linguistic structure.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other work has shown that infants continue to distribute fixations more to talkers' eyes and upper part of the face (Liu et al, 2011). Examinations of mothers' speech productions have shown distinct facial characteristics and exaggerated lip movement in ID speech (Shochi et al, 2009; Green et al, 2010; Shepard et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Most vowel contrasts in English can be approximated by modeling two components (Fromkin, 1964): vertical opening and horizontal spread. Studies of lip movements have revealed that, during the production of English vowels, lip shape is largely driven by the vertical opening (Fromkin, 1964; Green, Nip, Wilson, Mefferd, & Yunusova, 2010). Of course, horizontal spreading and rounding is also prominent for a small number of vowels (Fromkin, 1964; Stevens, 2000) and consonants (e.g., /w/; Chomsky & Halle, 1968; Stevens, 2000).…”
mentioning
confidence: 99%